HUBUNGAN KOMUNIKASI PEMASARAN DAN PROMOSI DENGAN KEPUTUSAN MEMILIH JASA LAYANAN KESEHATAN (STUDI PADA RUMAH SAKIT ISLAM LUMAJANG) - LESTARI, SINTA PETRI (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:competition in the business world becomes more intense, confronts the uncertain situation. nota few companies out of business because no longer able to maintain the viability of their business.This phenomenon occurs as a result of the competitive business world competition and each companywould like to win the competition. The company's core competition need to be explored in order tocreate competitive advantage by using the right marketing communication strategy. Companies alsoneed to use your strengths and minimize kelemahana to seize market opportunities. the existence ofmany rivals in the business world will be able to become a benchmark for the company. in a sensecan be a motivation in running the business. it also applies to those businesses in the health servicesindustry, whether it be hospitals, health centers and private practitioners, in order to live and developthe necessary skills and knowledge in strategic marketing communications. Health is one of the basichuman needs. Healthy itself is a state of optimal physical, mental and social, and not just limited tothe state of being free of any disease or infirmity. the hospital is one part of the health service. Fromthe data processing and research, it is known marketing communications and promotion of the rightto use RSI Lumajang in order to increase the number of visitors and the people who come and pickRSI Lumajang as health services. From these results can be made suggestions that might benefitLumajang RSI to determine the right marketing strategy.